Public relations for Asia - Morris, Trevor (Palgrave Macmillan, 2008)
This book is an essential read for anyone interested in Public Relations in Asia. Combining the latest in Public Relations theory with practical guidance on how to plan and structure a PR campaign and top tips on how to create successful PR campaigns, this book is also full of case histories from Asia and the rest of the world